Bantuan Hukum sebagai Hak Azazi Manusia bagi Kelompok Guru PGRI Bangkinang - Yuli Heriyati; Citra Ayu (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service project aims to enhance the understanding of teachers in PGRI Bangkinang regarding their legal rights, particularly in accessing legal aid. Many teachers in remote areas are unaware of their legal rights, which leads to limited access to adequate legal assistance. The method used in this project is a participatory approach through legal education delivered in the form of workshops and group discussions. The activity also includes case simulation to provide practical understanding to participants. The results show a significant improvement in the teachers' understanding of their legal rights, with over 80% of participants feeling more prepared and confident in facing potential legal issues. Additionally, the project successfully opened access for teachers to learn how to access available legal aid services. This activity also creates a long-term impact by establishing a sustainable legal support system for teachers in Bangkinang, ensuring they are better protected and able to focus on their educational duties.